Communication and mental illness : theoretical and practical approaches - France, Jenny; Kramer, Sarah, 1969- (Jessica Kingsley Publishers, 2001)
Annotation Communication and Mental Illness is a comprehensive and practical textbook which presents the key themes in the practice of speech therapy in psychiatry. It describes communication problems associated with different kinds of disorders, including the autistic spectrum disorders, and details practical techniques which can be applied to them.